KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN DISPOSISI MATEMATIS SISWA SMP MELALUI PENDEKATAN KONTEKSTUAL - Indri Nopianti Dewi; Padillah Akbar; Muhammad Afrilianto (Departement of Mathematics Education, 2019)
This study intended to studied student’s ability to mathematical creative thinking and mathematical disposition of student who receive contextual approach compared to those who receive regular learning. Method use in this study is Experiment Method. Population in this study is the students of Junior High School in West Bandung Regency while the sample is SMP Negeri 1 Cihampelas and two classes are randomly chosen from all existing VII grade. From those two classes randomly appointed which will be the experiment class and control class. Experiment Class receive learningwith contextual approach while Control Class receive regular learning. Instrument used are mathematical creative thinking ability test and mathematical disposition scale. From the result and hypothesis testing concluded that increasing ability to mathematical creative thinking and mathematical disposition of students who receive contextual approach learning are better than those that receive regular learning.